PERBANDINGAN ANTARA ROE DENGAN EVA DALAM MENILAI KINERJA KEUANGAN - Andika Setiawan; Fanny Suzuda Pohan (REMITTANCE: JURNAL AKUNTANSI KEUANGAN DAN PERBANKAN, 2021)
There were several ways that could be used to assess the company's financial kinerjance, one of them is by using the Return On Equity. Return On Equity measured the company's ability to earn profits from its capital. This ratio also had weaknesses, among others, this ratio does not use the cost of capital. To overcome this, there was another alternative in assessing the company's kinerjance, namely using Economic Value Added (EVA). This study aimed to determine whether there is a difference between Return on Equity and Economic Value Added in assessing the financial kinerjance of Food and beverage companies on the Indonesia stock exchange in the period 2015 – 2019.The research sample consisted of 16 companies with 80 research data. Sampling used purposive sampling. Analysis of the data in this study using the SPSS Statistics 26 software program with the analysis technique of the Paired Sample T Test. The results of this study indicate that there is a significant difference between Return On Equity and Economic Value Added in assessing the financial kinerjance of Food and beverage companies due to the Economic Value Added including the calculation of the cost of capital.